Formulation of Entomopathogenic Nematodes for the Control of Key Pests of Grapevine: A Review - Nxitywa, A.; Malan, A.P. (South African Journal of Enology and Viticulture, 2021)
Entomopathogenic nematodes (EPNs) are insect parasites that are used successfully as biological control agents against key pest insects of grapevine. To achieve low chemical residues and the sustainable production of grapes, it is important that biological control agents such as entomopathogenic nematodes for the control of grapevine insect pests be incorporated in an integrated pest management system for grape production. However, the commercialisation and large-scale use of EPNs is limited by their short shelf life in formulations and in storage, thus leading to poor quality and reduced efficacy against insects in the field. In South Africa, interest in the use of EPNs within an integrated pest management system has grown over the past two decades, therefore developing a formulation technique with an acceptable storage survival period, while maintaining infectivity, is essential. Moreover, the successful control of insects using EPNs is only achievable when the formulated product reaches the end user in good condition. This review is focused on the different types of formulations required for storage and ease of transport, together with the application formulation for above-ground pests and the factors affecting them. The quality assessment, storage and handling of formulated EPNs are also discussed.